Implementation of PV - Based Boost Converter Using PI Controller with PSO Algorithm (International Journal of Engineering and Computer Science, 2017)
This paper presents the maximum power point tracking (MPPT) technique for increasing the output voltage of the photovoltaic (PV) system. In order to increase the output voltage of the system, boost converter is connected to the PV system. However, when connecting the boost converter to the PV system the voltage value at the output equal to the input voltage. According to the principle of boost converter, output voltage must be higher than the input voltage. The output voltage depends upon the switching frequency and duty cycle of the converter. As to increase the output voltage of the PV system based on boost converter characteristics. The control strategies can be used based on the combination between the Particle Swarm Optimization (PSO) method and the Proportional Integral (PI) controller that strategies can be extract the maximum power from a PV system. The PI Controller is used to tracking the maximum power from the PV panel, at different atmospheric condition. The Solar PV power generation system is comprised several elements like solar panel, DC-DC converter, MPPT Control Strategies and load.The Simulation result from MATLAB/SIMULINK is presented to verify the performance of the converter.